Evaluation of the effect of an orthoptic exercise through a fencing mask on postural regulation and sporting gesture - Lefils, O.; Bertucci, W.; Lefils-Capitain, C. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
From a preliminary study, we observed that high-level fencers suffered as much disruption to the posture regulation by the port of a fencing mask as a controlled population who had never practiced this sporting activity. The orthoptic balances revealed significant disorders with the mask around the visual field for the whole group and the convergent fusional capacities for 95% of them.